Evaluating the introduction of COVID-19 oral antivirals through a test and treat program: outcomes from a cohort study in four African countries - Jessica T. Joseph; Maria Grau-Sepulveda; Bridget C. Griffith; Norman Lufesi; Alexander Martin-Odoom; Nyuma Mbewe; Mwaba Mulenga; Shanti Narayanasamy; Lawrence Ofori-Boadu; Christian Ramers; Edson Rwagasore; Dyson Telela; et al. (International Journal of Infectious Diseases, 2025)
Introduction: Access to oral antivirals like nirmatrelvir/ritonavir to treat COVID-19 remains largely unavailable across Africa. Ghana, Malawi, Rwanda and Zambia, all members of the COVID Treatment QuickStart Consortium, leveraged existing infrastructure to rapidly commence COVID-19 test-and-treat programs. We describe the individual-level impact within the cascade of care. Methods: A retrospective cohort study was conducted in 36 facilities across four countries that captured data on SARS-CoV-2 positive individuals who were screened for treatment. Treatment criteria included being high-risk for severe COVID-19 disease progression, presenting within five days of symptom onset, and having mild-to-moderate COVID-19 disease severity; treatment eligibility was ultimately determined by trained healthcare workers. Results: From 1941 participants, 50.2% were determined eligible while 65.2% were prescribed nirmatrelvir/ritonavir. Among those prescribed, 1265 (73.2%) received follow-up, among whom 99.4% confirmed treatment initiation and 97.6% completed the five-day treatment course. Two serious adverse events were reported, but neither was attributed to nirmatrelvir/ritonavir. Conclusions: These data are the first to suggest COVID-19 oral antiviral treatment can be quickly, efficiently and safely deployed in lower- and middle-income countries, in parallel with implementation research. Programs rapidly integrated their COVID-19 response into existing health service infrastructure, allowing for decentralization and demonstrating that introducing newly developed diagnostics and treatment in government health systems is feasible in lower-resourced settings during health emergencies. Equitable and timely access to diagnostics and treatments is crucial to combat emerging global disease threats and achieve global health equity.